2011
DOI: 10.5336/medsci.2011-24144
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Midodrine Hydrochloride on Chronic Hypotension in Patients with Diabetes Mellitus Undergoing Hemodialysis Therapy

Abstract: A AB BS S T TR RA AC CT T O Ob b j je ec c t ti i v ve e: Chro nic hypo ten si on is a com mon comp li ca ti on of he mo di aly sis in pa ti ents with di a be tes mel li tus. Mi dod ri ne hydroch lo ri de is an alp ha-1 ago nist that ef fec ti vely cor rects intra di aly tic hypo ten si ve at tacks. However, the ef fect of mi dod ri ne on chro nic hypo ten si on is still unk nown in he mo di aly sis pa ti ents. In the pre sent study, we ai med to eva lu a te the ef fects of mi dod ri ne tre at ment on chro nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A more recent study including 21 diabetic patients with chronic hypotension defined as systolic blood pressure less than 100 mmHg before dialysis found that midodrine therapy was associated with 10 mmHg and 5 mmHg increases in systolic and diastolic blood pressure, respectively. Vertigo and syncope significantly improved with midodrine therapy 26 . Again, no substantial side effects were noted.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A more recent study including 21 diabetic patients with chronic hypotension defined as systolic blood pressure less than 100 mmHg before dialysis found that midodrine therapy was associated with 10 mmHg and 5 mmHg increases in systolic and diastolic blood pressure, respectively. Vertigo and syncope significantly improved with midodrine therapy 26 . Again, no substantial side effects were noted.…”
Section: Discussionmentioning
confidence: 95%
“…Despite these observations of the safety of midodrine in the dialysis population 13,26 , intradialytic hypotension remains a significant risk factor for mortality among ESRD patients 1819 . The present study advances knowledge of the outcome implications of symptomatic hypotension by identifying pretransplant midodrine use, a measure of clinically significant hypotension, as a risk marker for complications after kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%